2017
DOI: 10.3390/nu9070659
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin C Influence Neurodegenerative Diseases and Psychiatric Disorders?

Abstract: Vitamin C (Vit C) is considered to be a vital antioxidant molecule in the brain. Intracellular Vit C helps maintain integrity and function of several processes in the central nervous system (CNS), including neuronal maturation and differentiation, myelin formation, synthesis of catecholamine, modulation of neurotransmission and antioxidant protection. The importance of Vit C for CNS function has been proven by the fact that targeted deletion of the sodium-vitamin C co-transporter in mice results in widespread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 205 publications
(289 reference statements)
2
100
2
6
Order By: Relevance
“…Some articles demonstrated the association between poor vitamin C and increased depression symptoms [70,71], between DM and depression [72] and between severe PD [73] and depression. Studies have shown that depression is a consequence of inadequate levels of ascorbic acid [74].…”
Section: Discussionmentioning
confidence: 99%
“…Some articles demonstrated the association between poor vitamin C and increased depression symptoms [70,71], between DM and depression [72] and between severe PD [73] and depression. Studies have shown that depression is a consequence of inadequate levels of ascorbic acid [74].…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbate (vitamin C) is a potent antioxidant obtained through the diet. In the brain, ascorbate is maintained at high concentrations relative to other organs [ 13 ], and low levels are linked to neurodegenerative diseases [ 14 , 15 ]. Previous research has indicated that patients with Parkinson’s disease have significantly lower concentrations of plasma ascorbate and higher concentrations of oxidative stress markers compared to healthy controls [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its ability to effectively disrupt the fibrillogenesis of the A β peptide has already been reported [ 30 ]. Vitamin C ((2R)-2-[(1S)-1,2-dihydroxyethyl]-3,4-dihydroxy-2H-furan-5-one) is believed to be a vital antioxidant in the brain ( Figure 1(b) ) [ 31 ]. Namely, a huge body of evidence suggests that vitamin C may change the course of neurological diseases and serve as a potential therapeutic tool.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, a huge body of evidence suggests that vitamin C may change the course of neurological diseases and serve as a potential therapeutic tool. Intracellularly, it helps to maintain several key processes, including neuronal maturation and differentiation, myelin formation, synthesis of catecholamine, modulation of neurotransmission, and antioxidant protection [ 31 ]. Targeted deletion of the sodium-vitamin C cotransporter in mice resulted in widespread cerebral hemorrhage and death [ 31 ].…”
Section: Introductionmentioning
confidence: 99%